Mathematical Resilience dalam Perspektif Filsafat Pendidikan Matematika - Nena Meilan; Varialya Kayla Azzahra; Anggun Badu Kusuma (Griya Journal of Mathematics Education and Application, 2026)
Mathematical resilience is a student’s ability to persevere, remain confident, and maintain a positive attitude when facing difficulties in learning mathematics. Low mathematical resilience can lead to math anxiety, low motivation to learn, and a decline in academic achievement. Although it has been extensively studied from psychological and pedagogical perspectives, research examining mathematical resilience from the perspective of the philosophy of mathematics education remains limited. This article aims to analyze the concept, influencing factors, and implications of mathematical resilience in mathematics learning. The study employs a literature review method by analyzing articles published between 2019 and 2026 from the Google Scholar and ERIC databases. The findings indicate that mathematical resilience encompasses the dimensions of value, struggle, growth, support, and culture, which are influenced by cognitive, psychological, and social factors. The absolutist paradigm tends to hinder the development of resilience, whereas constructivism and fallibilism support it by accepting mistakes as part of the learning process. These findings underscore the importance of a psychologically safe learning environment, as well as the implementation of productive struggle and open-ended problems to enhance students’ mathematical resilience.